Kajian Pemakaian Bata Semen Dengan Agregat Limbah Gergajian Kayu Sebagai Bahan Dinding Kontruksi Gedung - Hartono Hartono (Politeknik Negeri Semarang, 2011)
Waste of sawn wood powder came from different parts of the sawmill industry, because they were abundant, giving rise to pollution that interferes with the surrounding environment, if there is no need usually discarded / burned so just.For waste of sawn wood powder can be used as a substitute for fine aggregate or sand mixed with a certain ratio of cement to be utilized as building materials as brick cement.Product obtained in the laboratory experimental illustration of the identification of variations in the change ratio of the mixture, powdered cement and sawn timber, with comparisons based on the volume value of the maximum compressive strength of masonry cement mix 1 pc : 2 the sawn wood powder able to achieve 101.2 kg/cm2 > 100 kg/cm2 compressive strength of the solid red brick is allowed (SII-0021-78). Analysis of the ability of the compressive strength of cement bricks for construction of building walls, cement brick with a mixture of 1 pc : 7 parts sawdust powder according to the SII-0021-78, including the type of solid brick class 25 kg/cm2 compressive could reach 25.55. So cement bricks can be used for building construction which carry a maximum load of 25 kg/cm2 with a compressive strength of the lighter weight of the bricks in the market.